PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI DAN KEPUASAN PENGGUNA ACCURATE TERHADAP KINERJA INDIVIDU - Raminda, All Natri Ayu (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to test and analyze some factors that influence individual performance of the users of ACCURATE accounting system on PT Multi Bangun Sarana di Surabaya, i.e.: system quality, information quality, and the satisfaction of the users of ACCURATE accounting system. The researcher processes the primary data which is in the form of questionnaires that have been issued to 30 respondents, in which the respondents are the employees of PT Multi Bangun Sarana Surabaya which use ACCURATE accounting system. The multiple linear regressions analysis and the SPSS 20 application are used as the analysis technique. The result of the research shows that system quality has been proved significantly has positive influence to the individual performance. The usersâ satisfaction has been proved significantly has positive influence to the individual performance. And information quality has not been proved significantly has influence to the individual performance. In this research information quality does not have any significant to the individual performance since there are some factors that can influence it i.e.: information that is required by the employees can be obtained not only from ACCURATE accounting system, and the users of ACCURATE accounting system cannot trust the information that has been obtained by ACCURATE accounting system.Keywords: Quality of the System, Quality of the Information, Satisfaction of the Users, the Individual Performance.